Confirmation of ξ1 CMa's ultra-slow rotation: magnetic polarity reversal and a dramatic change in magnetospheric UV emission lines. Issue 2 (25th May 2021) - Erba, C; Shultz, M E; Petit, V; Fullerton, A W; Henrichs, H F; Kochukhov, O; Rivinius, T; Wade, G A
ABSTRACT: The magnetic β Cep pulsator ξ 1  CMa has the longest rotational period of any known magnetic B-type star. It is also the only magnetic B-type star with magnetospheric emission that is known to be modulated by both rotation and pulsation. We report here the first unambiguous detection of a negative longitudinal magnetic field in ξ 1  CMa (〈 Bz 〉 = −87 ± 2 G in 2019 and 〈 Bz 〉 = −207 ± 3 G in 2020), as well as the results of ongoing monitoring of the star's H α variability. We examine evidence for deviation from a purely dipolar topology. We also report a new HST UV spectrum of ξ 1  CMa obtained near magnetic null that is consistent with an equatorial view of the magnetosphere, as evidenced by its similarity to the UV spectrum of β Cep obtained near maximum emission. The new UV spectrum of ξ 1  CMa provides additional evidence for the extremely long rotation period of this star via comparison to archival data.